Fault location scheme for multi-terminal DC transmission systems using time signal extraction and distance vector analysis - Jingfeng Mao; Yang Wu; Xiuyong Yu; Jiawen Qiu; Aihua Wu; Xinsong Zhang (International Journal of Electrical Power & Energy Systems, 2025)
Multi-terminal direct current transmission systems face significant challenges in accurate fault location due to complex wave propagation paths and interference from multiple reflected wavefronts, which can lead to protection failures and system instability. This paper presents an advanced fault location scheme that integrates time signal extraction with distance vector analysis to address these challenges. The scheme employs variational mode decomposition combined with maximum after squaring techniques to precisely calibrate traveling wave arrivals. This scheme extracts accurate time signals from complex fault waveforms. A novel fault section identification vector is then constructed by analyzing the relationship between measured time signals and inherent topological distances within the network, enabling accurate fault section determination without requiring precise wave velocity or terminal synchronization. Extensive simulations conducted on various fault scenarios demonstrate that the proposed scheme achieves location accuracy within 300 m across different fault types, locations, and resistances, while maintaining robust performance under noise conditions with signal-to-noise ratios down to 30 dB. The scheme shows superior accuracy compared to conventional traveling wave methods, particularly for remote faults where traditional techniques exhibit significant errors. These results indicate that the proposed time signal and distance vector scheme provides a reliable and practical solution for fault location in multi-terminal direct current networks, offering enhanced protection reliability and reduced maintenance costs for modern power transmission infrastructure.